A Case of Eosinophilic Gastroenteritis with Ascites. (24th December 2015) - Caglar, Erkan; Sezgin Caglar, Aslı; Gokturk, Suut; Dobrucali, Ahmet
Abstract : Eosinophilic gastroenteritis is a rare disorder of unknown cause characterized by focal or diffuse eosinophilic infiltration of gastrointestinal tract, especially the stomach and duodenum. Its clinical presentation depends on which segment of gastrointestinal tract is affected and on the depth of eosinophilic infiltration in the affected segment. We present a case of a 35-year-old male with abdominal distention for six months. Laboratory testing revealed elevated eosinophil count and serum immunoglobulin E (IgE) levels. In abdominal tomography, ascites was observed, and eosinophilic infiltration was detected in duodenum biopsy samples, collected during endoscopic examination of upper gastrointestinal system. Clinical and pathologic findings of the patient responded to steroid dramatically. Even though their comorbidity is rare, eosinophilic gastroenteritis should be considered in differential diagnosis of patients with unspecified ascites.